Original articleAnalysis of intracranial volume ratios by means of cerebrospinal fluid deployment indicators - Szczepek, Ewa; Czerwosz, Leszek Tomasz; Nowiński, Krzysztof; Czernicki, Zbigniew; Jurkiewicz, Jerzy (Folia Neuropathologica, 2015)
Introduction : Imaging studies make it possible not only to visualize the general structure of the brain but also to take precise measurements of brain tissue volume and the size of individual lobes and their structure. The aim of this study was to determine the ratio of cerebrospinal fluid (CSF) volume contained in the intracranial ventricular system to the brain tissue volume and the ratio of CSF volume in the subarachnoid space and basal cisterns to the brain tissue volume. Material and methods : The evaluation of volumetric measurements of computed tomographic (CT) images was undertaken on 23 male and female patients (average age 56.9 ± 6.1) diagnosed with normal pressure hydrocephalus (NPH) and 27 male and female patients (average age 70.6 ± 5.2) diagnosed with brain atrophy (BA). In the CT imaging studies, the total brain tissue volume and CSF volume collected in the intracranial fluid cavities were mapped to a colour scale. The VisNow software was used for volumetric evaluation. The groups were compared by means of the non-parametric Kolmogorov-Smirnov test (K-S) for independent samples. Paired data were compared by means of the nonparametric Wilcoxon test. Results : The volumes of brain (brain volume – BV) and cerebrospinal fluid (fluid volume – FV) differ greatly from each other in both groups BA and NPH. The SBR (subarachnoid space and basal cisterns-to-brain ratio) and VBR (ventricle-to-brain ratio) indicators differ significantly and very much within the NPH group as well as within the BA group. In the NPH group a clearly higher value of VBR can be observed in comparison with the BA group. There was a higher value of SBR in the BA than the NPH group. Conclusions : The simultaneous use of two indicators, VBR and SBR, on a study group of 50 patients enabled the total separation of NPH and BA groups. This differentiation can have real diagnostic value. Thus the volumetric assessment of the volume of CSF and brain tissue based on CT of the head can become an important part of the differential diagnosis of hydrocephalus and brain atrophy.